2017
DOI: 10.4103/1735-9066.202066
|View full text |Cite
|
Sign up to set email alerts
|

Comparative investigation of indicators of growth and behavioral disorders in children with normal, low, and very low birth weight at pre-school age in Isfahan during 2015

Abstract: Introduction:Birth weight is one of the most important indicators of infant's health and could predict their health condition in future. This study was conducted to determine and compare indicators of growth [weight, height, and body mass index (BMI)] and behavioral disorders in children with normal, low, and very low birth weight at pre-school age.Materials and Methods:In this descriptive analytical study, 236 children (126 with normal weight, 100 with low birth weight, and 10 with very low birth weight) at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…19 This study's results, however, are not in accordance with the study conducted by Ehsanpour S et al, which found that a slower growth rate is observed in babies with lower birth weight. 20 Cyanosis is a bluish discoloration of the skin and mucous membranes due to a decrease in hemoglobin levels ≥ 5 g/dL which indicates a decrease in blood oxygen supply to the tissue. 21 This study found that the incidence of cyanosis was more common in the group of very low birth weight preterm infants who experience weight gain not according to the target, although it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…19 This study's results, however, are not in accordance with the study conducted by Ehsanpour S et al, which found that a slower growth rate is observed in babies with lower birth weight. 20 Cyanosis is a bluish discoloration of the skin and mucous membranes due to a decrease in hemoglobin levels ≥ 5 g/dL which indicates a decrease in blood oxygen supply to the tissue. 21 This study found that the incidence of cyanosis was more common in the group of very low birth weight preterm infants who experience weight gain not according to the target, although it was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%